2000
DOI: 10.1097/00004694-200001000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Thirty consecutive patients with congenital spinal deformity underwent magnetic resonance imaging (MRI) to determine the incidence of occult intraspinal anomaly. These congenital spinal deformities included 29 cases of congenital scoliosis and one case of congenital kyphosis. Physical examination findings and plain radiographs were reviewed in an attempt to correlate these findings with subsequent intraspinal pathology. Nine patients had intraspinal anomalies identified on MRI consisting of five with tethered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 5 publications
3
23
0
Order By: Relevance
“…Prahinski et al [25] reported 9 cases with intraspinal abnormalities after MRI screening of 30 cases of CS. Only 3 of these 9 had plain radiographs and physical examination findings suggestive of their intraspinal abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prahinski et al [25] reported 9 cases with intraspinal abnormalities after MRI screening of 30 cases of CS. Only 3 of these 9 had plain radiographs and physical examination findings suggestive of their intraspinal abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the priority for a patient suspected of having SSCM should be CTM examination. With the evolution and further accessibility of modern neuroimaging techniques, this condition is becoming more frequently diagnosed [24,25,26,27,28]. Pang et al [9,20] recommended that MRI should be performed in patients with myelomeningocele with unusual clinical features, such as inconsistencies between placode and neurological level and right-left asymmetries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that 20 to 40% of children with either congenital,1 2 3 4 5 infantile,6 or juvenile7 8 scoliosis have a spinal cord abnormality on preoperative MRI studies. Many of these will require neurosurgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…2 3 4 5 6 7 8 Historically, patients with scoliosis associated with a tethered cord were treated in a staged fashion, with a tethered cord release first, followed by scoliosis correction 6 weeks to 6 months later, due to concerns of neurological injury 39 10 11 Recent advances in neurophysiological monitoring techniques, however, have greatly increased the margin of safety for procedures with the potential for neurological injury.…”
mentioning
confidence: 99%